Thermal performance in circular tube fitted with coiled square wires - Promvonge, Pongjet (My University, 2008)
The effects of wires with square cross section forming a coil used as a turbulator on the heat transfer and turbulent flow friction characteristics in a uniform heat flux, circular tube are experimentally investigated in the present work. The experiments are performed for flows with Reynolds numbers ranging from 5000 to 25,000. Two different spring coiled wire pitches are introduced. The results are also compared with those obtained from using a typical coiled circular wire, apart from the smooth tube. The experimental results reveal that the use of coiled square wire turbulators leads to a considerable increase in heat transfer and friction loss over those of a smooth wall tube. The Nusselt number increases with the rise of Reynolds number and the reduction of pitch for both circular and square wire coils. The coiled square wire provides higher heat transfer than the circular one under the same conditions. Also, performance evaluation criteria to assess the real benefits in using both coil wires of the enhanced tube are determined. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Coiled wire; Enhancement efficiency; Heat transfer enhancement; Turbulators; Wire shape